2001
DOI: 10.1021/jf001363l
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aroma Differences between Hand-Squeezed Juices from Valencia Late and Navel Oranges by Quantitation of Key Odorants and Flavor Reconstitution Experiments

Abstract: Twenty-five odor-active compounds were quantified in hand-squeezed juices of Valencia late and Navel oranges using stable isotope dilution assays. Odor activity values (OAVs, ratio of the concentration to odor thresholds) based on odor thresholds in water were calculated for the entire set of aroma compounds in both varieties. It was shown that due to their high OAVs, the fruity-smelling esters ethyl 2-methylpropanoate, ethyl butanoate, (S)-ethyl 2-methylbutanoate, and 3a,4,5,7a-tetrahydro-3,6-dimethyl-2(3H)-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
196
1
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(208 citation statements)
references
References 20 publications
7
196
1
4
Order By: Relevance
“…Although 2,4,6-trimethyl-1,3,5-trioxane and 1,1,-diethoxy-ethane, as products from the condensation of acetaldehyde, were previously observed in fruit such as capers (Ozcan and Chalchat, 2007) and fermentative food such as grape wine (Lee and Noble, 2003) and pomaces (Ruberto et al, 2008), they have never been reported in citrus fruits, and in our study they were merely trivial constituents detected in emitted OVOCs. This profile of emitted OVOCs was consistent with that of OVOCs in citrus fruit flesh (Umano et al, 2002) or juice (Buettner and Schieberle, 2001;Brat et al, 2003), with ethanol, acetaldehyde, and ethyl acetate being the predominant compounds extracted. Also, the results in the study were quite similar to previous studies, which revealed that ethanol, ethyl acetate, 2-butanone and acetaldehyde typically showed high levels in odor sources such as municipal solid wastes (Staley et al, 2006) and waste treatment facilities (Eitzer, 1995;Smet et al, 1999;Dorado et al, 2014;Lehtinen et al, 2013).…”
Section: Flux Measurementsupporting
confidence: 78%
See 2 more Smart Citations
“…Although 2,4,6-trimethyl-1,3,5-trioxane and 1,1,-diethoxy-ethane, as products from the condensation of acetaldehyde, were previously observed in fruit such as capers (Ozcan and Chalchat, 2007) and fermentative food such as grape wine (Lee and Noble, 2003) and pomaces (Ruberto et al, 2008), they have never been reported in citrus fruits, and in our study they were merely trivial constituents detected in emitted OVOCs. This profile of emitted OVOCs was consistent with that of OVOCs in citrus fruit flesh (Umano et al, 2002) or juice (Buettner and Schieberle, 2001;Brat et al, 2003), with ethanol, acetaldehyde, and ethyl acetate being the predominant compounds extracted. Also, the results in the study were quite similar to previous studies, which revealed that ethanol, ethyl acetate, 2-butanone and acetaldehyde typically showed high levels in odor sources such as municipal solid wastes (Staley et al, 2006) and waste treatment facilities (Eitzer, 1995;Smet et al, 1999;Dorado et al, 2014;Lehtinen et al, 2013).…”
Section: Flux Measurementsupporting
confidence: 78%
“…Alcohols dominated in released OVOCs and were followed by esters, ketones and aldehydes (Table 1, Fig. 2), just as those detected in citrus fruit flesh (Umano et al, 2002) and juice (Buettner and Schieberle, 2001;Brat et al, 2003) and in intermediates of aerobic metabolism of organic materials (Eitzer, 1995;Staley et al, 2006). Alcohols were also observed as major VOCs emitted from green wastes (lawn clippings, yard prunings, and food wastes, as well as green and woody wastes) (Kumar et al, 2011) and biowastes (70% garden waste, 20% kitchen waste and 10% nonrecyclable paper) (Smet et al, 1999) during the aerobic composting process.…”
Section: Flux Measurementmentioning
confidence: 90%
See 1 more Smart Citation
“…The aroma of fresh squeezed orange juice has been perceived as one characteristic distinguishing it from processed orange juices (Buettner & Schieberle, 2001). The one-way ANOVA results (within the control group) indicated that consumers did not significantly distinguish the flavor (p=0.39) and aroma (p=0.08) of fresh squeezed orange juice but, they significantly distinguished the color (p<0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that commercial brand orange juice, even of the same brand, comes in different varieties, depending on availability. While orange varieties can affect sensory properties (Buettner & Schieberle, 2001), Lotong, Chambers, & Chambers (2003) found that the flavor of most commercial orange juice brands is not differentiable based on sensory characteristics.…”
Section: Samplesmentioning
confidence: 99%